Can we use structural knowledge to design a protective vaccine against HIV‐1?. (27th November 2019) - Bjorkman, Pamela J.
Abstract : Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) remains one of the most important current threats to global public health. Since its identification in the early 1980s, at least 75 million people have been infected with HIV‐1, the virus that causes AIDS. Although antiretroviral drugs are effective at prolonging life after infection in the developed world, they are associated with significant side effects and are not in widespread use in the developing world. The best way to control the AIDS epidemic would be a vaccine that protects against infection by HIV‐1. Most vaccines work by inducing antibodies in serum or mucosa that block infection or prevent invasion of the bloodstream. Here, I describe background related to my laboratory's attempts to develop an immunogen that would elicit protective antibodies against HIV‐1.